Cyclen-based Gd3+ complexes as MRI contrast agents: Relaxivity enhancement and ligand design. Issue 22 (15th November 2016) - Rashid, Haroon Ur; Martines, Marco Antonio Utrera; Jorge, Juliana; de Moraes, Paula Martin; Umar, Muhammad Naveed; Khan, Kamin; Rehman, Hanif Ur
Graphical abstract: Abstract: Magnetic Resonance Imaging (MRI) is a noninvasive radiology technique used to examine the internal organs of human body. It is useful for the diagnosis of structural abnormalities in the body. Contrast agents are used to increase the sensitivity of this technique. 1, 4, 7, 10-Tetraazacyclododecane (cyclen) is a macrocyclic tetraamine. Its derivatives act as useful ligands to produce stable complexes with Gd 3+ ion. Such chelates are investigated as MRI contrast agents. Free Gd 3+ ion is extremely toxic for in vivo use. Upon complexation with a cyclen-based ligand, it is trapped in the preformed central cavity of the ligand resulting in the formation of a highly stable Gd 3+ -chelate. Better kinetic and thermodynamic stability of cyclen-based MRI contrast agents decrease their potential toxicity for in vivo use. Consequently, such agents have proved to be safest for clinical applications. Relaxivity is the most important parameter used to measure the effectiveness of a contrast agent. A number of factors influence this parameter. This article elucidates detailed strategies to increase relaxivity of cyclen-based MRI contrast agents. 1, 4, 7, 10-Tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA) and 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7-triacetic acid (DO3A) are two key ligands derived from cyclen. They also act as building blocks for the synthesis of novel ligands. A few important methodologies for the synthesis of DOTA and DO3A derivatives are described. Moreover, the coordination geometry of chelates formed by these ligands and their derivatives is discussed as well. Novel ligands can be developed by the appropriate derivatization of DOTA and DO3A. Gd 3+ -chelates of such ligands prove to be useful MRI contrast agents of enhanced relaxivity, greater stability, better clearance, lesser toxicity and higher water solubility.